1995
DOI: 10.7326/0003-4819-122-3-199502010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic Immunologic Manifestations in Chronic Hepatitis C and Hepatitis C Virus Serotypes

Abstract: We confirm that the prevalence of extrahepatic immunologic abnormalities is high in patients with chronic hepatitis C. These abnormalities may occur in patients infected with any of the three major hepatitis C virus serotypes now present in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
159
5
6

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 315 publications
(183 citation statements)
references
References 0 publications
7
159
5
6
Order By: Relevance
“…Moreover, asymptomatic immunologic changes have been reported in this type of infection, such as RF in 71% of patients and ANA in 22% of patients (9).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, asymptomatic immunologic changes have been reported in this type of infection, such as RF in 71% of patients and ANA in 22% of patients (9).…”
Section: Discussionmentioning
confidence: 97%
“…Latent autoimmune thyroid disease, glomerulonephritis, polymyositis, and pulmonary fibrosis have been reported in association with HCV (5)(6)(7)(8). Lymphocytic sialadenitis has been reported in patients with chronic HCV infection, but the clinical and immunologic status of those patients was not described (9). Retrospective studies have reported the presence of antibodies against HCV in 10% of patients with sicca symptoms, but the actual prevalence of HCV infection associated with Sjogren's syndrome remains a subject of controversy (10).…”
mentioning
confidence: 99%
“…It is well known that some types of cryoglobulinemia are related to HCVinfection (6), and glomerulonephritis without cryoglobulinemia has also been reported to be accompanied with HCVinfection (7). In addition, a high prevalence of rheumatoid factor was reported in HCVpositive patients (8), although its immunological role is not yet well understood. On the other hand, manypatients with chronic hepatitis C have sialoadenitis like sicca syndrome (9).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis seems more severe in HBV-PAN, with 35% of deaths compared to 10% in patients with HCV infection. HCV-related vasculitis does not bear specific virologic features in term of genotype, viral load, or phylogenetic analysis (31)(32)(33). In contrast, in HBV-PAN most cases are associated with high levels of viral replication identified by high-serum HBV-DNA levels and hepatitis B antigen positivity, promoting the persistence of viral immune complexes in antigen excess (34).…”
Section: Pan-type Vasculitis Associated With Hcvmentioning
confidence: 99%